Abnormal upconversion luminescence induced by defects and Er3+–Yb3+ distance change in Cs3GdGe3O9:Er3+/Yb3+ phosphors. Issue 5 (23rd January 2023) - Cui, Hongqiang; Cao, Yongze; Zhang, Lei; Li, Ying; Zhang, Yuhang; Li, Lei; Zhang, Jinsu; Chen, Baojiu
Abstract: A series of Er 3+ /Yb 3+ co‐doped Cs3 GdGe3 O9 (CGG) phosphors were prepared by solid‐phase sintering method, and the microstructure and upconversion luminescence (UCL) properties were tested by variable‐temperature X‐ray diffractometry and variable‐temperature spectrometer. Abnormal UCL phenomena were found, which include UCL intensity continuously increasing under 980 nm laser continuous irradiation and UCL thermal enhancement. After 10 min of continuous irradiation by 980 nm laser at 513 K, the UCL intensity increased 2.91 times compared with the initial UCL intensity. The phenomenon is due to the electron releasing of host defects. The green UCL intensity of CGG:0.1Er 3+ /0.2Yb 3+ decreases at 303–423 K and increases at 423–723 K, which reaches 13.23 times compared with that at 423 K. The phenomenon is due to Er 3+ –Yb 3+ distance change by temperature and phonon‐assisted transitions. In addition, the absolute temperature sensitivities of samples are calculated by luminescence intensity ratio technology, the maximum absolute sensitivity of CGG:0.1Er 3+ /0.4Yb 3+ is 0.00691 K −1 at 546 K, and the maximum relative sensitivity of CGG:0.1Er 3+ /0.1Yb 3+ is 0.01224 K −1 at 303 K. These results indicate that CGG:Er 3+ /Yb 3+ phosphors can be used as a high‐temperature optical thermometer.